International Efforts in Combating Women Trafficking Within Human Rights Protection Framework International and National Measures to Combat Trafficking in Women - Al- Anzi, Abdul-Salam Housain (Journal of Ecohumanism, 2024)
The phenomenon of trafficking in women and the resulting multiple human rights violations has been one of the most complex challenges facing the international community, as this complexity is linked to different perspectives in finding a comprehensive definition of the phenomenon. Therefore, many international provisions have been interested in addressing this phenomenon, in an attempt to adapt, at each period, to the new forms and dimensions they take at each era. In line with the current situation, there are approaches that do not limit the mechanisms adopted to combat women trafficking issues to prevention, repression and punishment, but rather to address the root causes of this phenomenon, which relate to combating poverty, inequality and corruption